Long-lasting infection with Anaplasma ovis in sheep - Héctor Ruiz; Marta Ruiz de Arcaute; Alfredo Ángel Benito; Sergio Villanueva-Saz; José Calasanz Jiménez; Delia Lacasta (Veterinary Research Communications, 2024)
Ovine anaplasmosis is an emerging vector-borne disease in Europe caused by Anaplasma ovis . The infection has spread quickly in recent years, causing moderate to severe outbreaks in sheep flocks, leading to relevant economic losses in sheep farming. This wider spread has been associated with global warming and climate change, favouring the maintenance and life cycle of their main vector, the ticks. However, another epidemiological aspect could favour this quick spread. Long persistence infection of Anaplasma ovis has been proposed as a hypothesis in several articles but never scientifically proven. The results of the present study demonstrate that eight adult sheep, both naturally or experimentally infected, maintain Anaplasma ovis load in blood during their whole productive life (4 to 6 years), being permanently infected. In addition, the results suggest that A. ovis bacterial load can be constant or suffer fluctuations, as has been demonstrated in other Anaplasma species. Both aspects can be determinants in the epidemiology and the transmission of the infection.